2003
DOI: 10.1002/ijc.10932
|View full text |Cite|
|
Sign up to set email alerts
|

Differential expression of genes induced by resveratrol in LNCaP cells: P53‐mediated molecular targets

Abstract: Prostate cancer prevention by key elements present in human nutrients derived from plants and fruits has been confirmed in various cell cultures and tumor models. Resveratrol (RE), a phytoalexin, induces remarkable inhibitory effects in prostate carcinogenesis via diverse cellular mechanisms associated with tumor initiation, promotion and progression. Earlier studies have shown that RE alters the expression of genes involved in cell cycle regulation and apoptosis, including cyclins, cdks, p53 and cdk inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(80 citation statements)
references
References 48 publications
4
75
0
Order By: Relevance
“…50,51 Studies analyzing the effect of RES on cardiovascular disease have also shown that this molecule inhibits lipid peroxidation by a pathway that involves NF-kB inactivation. 52,53 Therefore, the apoptosis induced by RES in MCF-7 cells could be mediated by Bcl-2 through a PI3K-and NF-kB-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Studies analyzing the effect of RES on cardiovascular disease have also shown that this molecule inhibits lipid peroxidation by a pathway that involves NF-kB inactivation. 52,53 Therefore, the apoptosis induced by RES in MCF-7 cells could be mediated by Bcl-2 through a PI3K-and NF-kB-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, resveratrol can have a potent effect, even in low-doses, through the aryl hydrocarbon receptor [44] that plays an important role in cancer cells [45]. Resveratrol not only influences estrogen receptors, but down-regulates the nuclear factor-KB [46], another important therapeutic target. The nuclear factor-KB may even be influenced by gallic acid [47] (present in great amounts in T. pratensis), quercetin [48], (which was detected in T. repens) or coumaric acid [49] (present only in V. arvensis and A. schoenoprasum).…”
Section: Note: the Content Of Individual Phenolic Compounds In The Flmentioning
confidence: 99%
“…For instance, resveratrol-induced apoptosis has repeatedly been reported to be accompanied by increased caspase activity (Ferry et al, 2002;Kim et al, 2004;Wolter et al, 2001). In addition, resveratrol-induced apoptosis was shown to be associated with Bax mitochondrial translocation (Mahyar-Roemer et al, 2002), inhibition of AKT activity (Brownson et al, 2002), up-regulation of the oncogene suppressor p53 (Narayanan et al, 2003), and down-regulation of cyclin D1 (Joe et al, 2002). In other studies, resveratrol has been shown to act via c-Jun NH 2 -terminal kinase (JNK), as resveratrol-induced p53-dependent transcriptional activity and apoptosis were blocked upon expression of a dominant-negative mutant of JNK or upon disruption of JNK1 or JNK2.…”
Section: Introductionmentioning
confidence: 99%